THE INFLUENCE OF PSYCHOSOCIAL FACTORS AT WORK ON WORKER FATIGUE - Muhamad Iqbal (Departemen K3 FKM Universitas Halu Oleo, 2026)
Work fatigue is a condition of decreased physical and mental capacity due to excessive workload, which negatively impacts productivity, safety, and the overall health of workers. In Indonesia, the Workplace Wellbeing Score 2025 survey reported that more than 52% of employees experience burnout, with 27.8% of approximately 99,000 annual work accidents caused by fatigue. The prevalence of fatigue in the manufacturing and mining sectors reaches 40–60%, worsening post-pandemic due to long working hours, night shifts, and the economic burden of mental health, which amounts to 6.5% of GDP. The World Health Organization predicts that work fatigue will become the second leading cause of death after heart disease, with a significant contribution to millions of worker deaths each year. This study employed a quantitative descriptive-analytic cross-sectional design involving 88 workers at a manufacturing company. The sample was selected using stratified random sampling based on the Slovin formula, encompassing production workers and office staff, with inclusion criteria of permanent employees aged 18–55 years and a minimum of one year of work experience. Data were collected through a self-administered questionnaire that adapted the JCQ for psychosocial factors, an ergonomic scale of 1–5, and the Work Fatigue Assessment Questionnaire to evaluate musculoskeletal pain, ergonomic injuries, and energy/motivation levels. SPSS analysis included univariate and bivariate tests (p<0.05). The results show significant relationships only for work pressure (p=0.004; fatigue risk 69.2% vs. 35.5%) and job satisfaction (p=0.043; 66.7% vs. 40%), while other variables such as ergonomics, company/colleague/management support, stress, and job control were not significant. Key recommendations include managing pressure through workload adjustments and realistic targets, enhancing job satisfaction via recognition of achievements and a supportive climate, and long-term ergonomic interventions.